Maternal factors associated with early childhood caries among 3–5-year-old children with low socio-economic status in Trishal, Bangladesh - Haque, Farzana; Folayan, Morenike Oluwatoyin; Virtanen, Jorma Ilmari (Frontiers in Oral Health, 2023)
Early Childhood Caries (ECC) is more prevalent in nations where a larger portion of the population resides below the poverty line. This study aimed to evaluate the connections between maternal awareness, attitudes, practices related to oral health, and the occurrence of ECC among children aged 3-5 years in Bangladesh.This cross-sectional study focused on mother-child pairs, specifically targeting children aged 3-5 years from low socioeconomic backgrounds in Trishal, Bangladesh. Data collection involved assessing maternal knowledge, attitudes, and behaviors concerning oral health using a validated instrument. Clinical examinations were conducted to check for dental plaque on the upper central incisors' labial surfaces, and ECC was identified using the ICDAS II index criteria.Associations between maternal oral health knowledge, attitudes, behaviors, and children's plaque score and caries status were analyzed through multivariable logistic regression, accounting for confounding variables (child's age, gender, mother's age, education, and number of children).Results: Among the 532 mother-child pairs, 491 (93.2%) mothers were unaware of fluoride's role in preventing tooth decay, while 516 (97%) recognized the importance of using fluoridated toothpaste during brushing. Additionally, 520 (97.7%) mothers reported not knowing how to brush their child's teeth, and only 87 (16.4%) brushed their children's teeth twice daily. Visible dental plaque was observed in 420 (78.9%) children, and 321 (60.3%) had ECC. Multivariate logistic regression analysis revealed that the plaque score significantly correlated with ECC in the study population (AOR: 5.617, 95% CI: 3.511-8.987).Conclusions: Mothers of preschool children from low socioeconomic backgrounds exhibited insufficient knowledge and suboptimal oral health practices. Among the identified risk factors for ECC, the plaque score emerged as the sole significant factor in this population in Bangladesh. It is imperative to prioritize support and interventions aimed at improving oral hygiene practices to reduce ECC risk in this population.